2023
DOI: 10.3389/fpubh.2022.1062688
|View full text |Cite
|
Sign up to set email alerts
|

Social media use as a coping mechanism during the COVID-19 pandemic: A multidimensional perspective on adolescents' well-being

Abstract: IntroductionSocial media use was previously characterized as both a maladaptive coping mechanism, and a source of engagement with peers, suggesting an ambivalent effect. The present study explored how adolescents might use social media as a coping mechanism during the COVID-19 pandemic, using a multidimensional perspective on well-being.MethodsOur sample consisted of 259 Romanian teenagers aged 11–16 (M = 13.38, SD = 0.93, 57% males). We investigated the potential indirect effect of social media use, i.e., its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Similar findings have been reported by several studies across different countries (Branquinho et al, 2020;Chen F. et al, 2020;Ellis et al, 2020;Asanov et al, 2021). In other studies, it is reported that as a coping mechanism others turned to social media, especially first year students who relied more on these social networks as compared to postgraduate students to help them cope with isolation (Maftei et al, 2023). The availability of supportive structures and systems was found to be critical for building resilience among youth during and post COVID-19 lockdowns (Masten and Motti-Stefanidi, 2020).…”
Section: Figuresupporting
confidence: 84%
“…Similar findings have been reported by several studies across different countries (Branquinho et al, 2020;Chen F. et al, 2020;Ellis et al, 2020;Asanov et al, 2021). In other studies, it is reported that as a coping mechanism others turned to social media, especially first year students who relied more on these social networks as compared to postgraduate students to help them cope with isolation (Maftei et al, 2023). The availability of supportive structures and systems was found to be critical for building resilience among youth during and post COVID-19 lockdowns (Masten and Motti-Stefanidi, 2020).…”
Section: Figuresupporting
confidence: 84%
“…In particular, it may be that patients with mental disorders use social media and Internet to overcome social isolation and discrimination experienced during in-vivo interactions ( 54 ). Another possible reason is that people with pre-existing mental disorders—already reporting high levels of anxiety and stress symptoms—more frequently searched information online to overcome uncertainty and fears ( 55 ). It would be important to explore the relationship between use of social media and Internet and the levels of personal functioning of people with severe mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also found that frequent use of social media (> two hours per day) for personal purposes was more common among depressed than non-depressed students. It has been shown that there may be a mutual relationship between depression and using social media because excessive social media use appears to be associated with depressed mood and depressive symptoms predict increased frequency of social media use 37 . According to a systematic review, although there are contradictory results in regard to the effect of time and frequency of using social media platforms on young adults' mental health, most studies have reported a positive and signi cant correlation between social media use and depression.…”
Section: Discussionmentioning
confidence: 99%